MENINGKATKAN KEMAMPUAN BAHASA ANAK MELALUI METODE BERCERITA PADA ANAK USIA 5-6 TAHUN - Eneng Hemah; Tri Sayekti; Cucu Atikah (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2018)
Language ability in children group B paudInsya Cendikia Lebak-Banten is still low. This is caused by less interesting and varied methods and learning media. The use of interesting media such as storytelling through flannel cloth is expected to improve the language skill of group B children. This research aims to (1) to know the ability of the process of telling Children in improving the language skills of children group B in PAUD Insya Cendikia Lebak-Banten and (2) to know the improvement of language ability of children group B PAUD Insya Cendikia Lebak-Banten through story telling method. Methods in this research is action research method consisting of 2 cycles, cycle II as much as 3 times action. The subjects of the study were the children of B PAUD Insya Cendikia Lebak-Banten with the number of children 16 children aged 5-6 years, consisting of 5 boys and 11 girls. Data collection techniques through observation, field notes, interview notes and documentation. Data analysis technique is done descriptively qualitative and quantitative. The success criterion of action is if the average score of the class in improving the language ability reaches 75%. The result of the research shows that: (1) the process of applying flannel cloth media includes 3 stages, namely preparation stage, activity implementation stage, and evaluation phase; (2) in the first cycle increased from the pre action result by 27% to 36%, and in cycle II increased to 75%. So it can be concluded that the application of storytelling through flannel media can improve the language skill of children group B PAUD Insya Cendikia Lebak-Banten.